Comparison of Transformational Leadership Models and Transactional Leadership Models - Wahyudi, Wahid (ProBisnis : Jurnal Manajemen, 2024)
The purpose of this study is to obtain an overview of the application of transformational and transactional leadership in government agencies. And to find out empirical studies related to the comparison of the application of transformational and transactional leadership in government agencies. This study uses a Systematic Literature Review (SLR) research approach, namely conducting the process of identification, evaluation, and interpretation of all available research that is relevant to the formulation of the problem or topic area being studied. The results of the study can be concluded that the application of transformational leadership and transactional leadership in government agencies is a breakthrough and innovation in managing public organizations to achieve organizational goals. This is considered important to provide a more dynamic public organizational climate over time. On the other hand, it should be realized that transformational and transactional leadership each have advantages and disadvantages in their application. In the context of these two leadership styles, what should not be ignored is the influence of situational variables on the implementation of this leadership